Employee Performance Evaluation at IPDN North Sulawesi Campus - Ayu Anjani Turangan; Itje Pangkey; Wilson Bogar (Journal of Social Science, 2022)
Human Resources are the main principle in an organization to achieve the expected goals. The performance of employees, especially at the Institute of Domestic Administration (IPDN) North Sulawesi Campus, requires evaluation, especially for civil service educators, namely caregivers. This study aimed to determine the performance and factors that affect the performance of employees (caregivers) at IPDN North Sulawesi Campus. The research used a qualitative approach, while the data collection techniques in this study are observation, interviews, and documentation. The informants in this study were the Head of the Civil Service Administration, the Head of the Parenting Subdivision, the employees (caregivers), and the IPDN Praja North Sulawesi Campus. In general, the results of this research are; 1) The performance of employees (caregivers) of IPDN North Sulawesi Campus is in a reasonably good category, this is based on the results of research where from five employee performance indicators, there are still two indicators included in the good enough category, namely “service orientation and work discipline, 2) Factors that affect the performance of employees (caregivers) of IPDN North Sulawesi Campus, there are four namely a) HR development, b) work motivation, c) supervision and d) work environment. It can also be seen that of the four factors that affect employee performance, only one factor supports the performance of IPDN North Sulawesi Campus employees, namely the work environment. In comparison, the other factors are HR development and work motivation. Furthermore, supervision does not support IPDN North Sulawesi Campus employees (caregivers) taking out the job.